Electrospun Nanofibers Loaded with Plantago major L. Extract for Potential Use in Cutaneous Wound Healing - Javier M. Anaya-Mancipe; Vanessa M. Queiroz; Rafael F. dos Santos; Rosane N. Castro; Verônica S. Cardoso; Alane B. Vermelho; Marcos L. Dias; Rossana M. S. M. Thiré (MDPI AG, 2023)
Plantago major L. is a plant available worldwide that has been traditionally used for several medical applications due to its wound healing, anti-inflammatory, and antimicrobial properties. This work aimed to develop and evaluate a nanostructured PCL electrospun dressing with P. major extract encapsulated in nanofibers for applications in wound healing. The extract from leaves was obtained by extraction in a mixture of water:ethanol = 1:1. The freeze-dried extract presented a minimum inhibitory concentration (MIC) for Staphylococcus Aureus susceptible and resistant to methicillin of 5.3 mg/mL, a high antioxidant capacity, but a low content of total flavonoids. Electrospun mats without defects were successfully produced using two P. major extract concentrations based on the MIC value. The extract incorporation in PCL nanofibers was confirmed using FTIR and contact angle measurements. The PCL/P. major extract was evaluated using DSC and TGA demonstrating that the incorporation of the extract decreases the thermal stability of the mats as well as the degree of crystallinity of PCL-based fibers. The P. major extract incorporation on electrospun mats produced a significant swelling degree (more than 400%) and increased the capacity of adsorbing wound exudates and moisture, important characteristics for skin healing. The extract-controlled release evaluated using in vitro study in PBS (pH, 7.4) shows that the P. major extract delivery from the mats occurs in the first 24 h, demonstrating their potential capacity to be used in wound healing.